INTEGRASI INDEKS KEMISKINAN MULTIDIMENSI DALAM SISTEM AKUNTANSI PUBLIK UNTUK MENDORONG AKUNTABILITAS SOSIAL PEMERINTAH - Arimi, Sailal; Harmaini, Harmaini; Hafdhallah, Hafdhallah (Worksheet : Jurnal Akuntansi, 2025)
Poverty is no longer measured solely by a lack of income, but is increasingly understood as a condition of deprivation across multiple dimensions of life. This study aims to measure the Multidimensional Poverty Index (MPI) of households in Indonesia using the Alkire-Foster (AF) method, utilizing data from the 2014 Indonesia Family Life Survey (IFLS), which remains the most recent wave conducted by the RAND Corporation. In addition, the study decomposes the MPI by geographic location (rural and urban areas) and calculates the contribution of each dimension and indicator to the overall MPI in both regions. The analysis reveals that 21.7% of households in Indonesia experience multidimensional poverty. On average, multidimensionally poor households suffer from 62% deprivation across the selected indicators, resulting in a national MPI score of 0.35. This figure reflects both the incidence and intensity of multidimensional poverty in Indonesia. The decomposition results indicate that multidimensional poverty is more prevalent in rural areas compared to urban areas, in terms of both incidence and intensity. Cumulatively, the standard of living dimension contributes the most to the MPI, accounting for 59.06% in rural areas and 51.19% in urban areas.